Perbandingan Metode WP dan SAW dalam Sistem Pendukung Keputusan untuk Menentukan Tingkat Keberhasilan Guru Mengajar di Tingkat SMK - Harmayani Harmayani; Reza Arvania Harahap (STMIK Budi Darma, 2022)
To improve student learning achievement, the learning process must take place well with the support of teachers who have competence, and the spirit of the teacher. In the current situation, schools do not have a system that can help assess the level of teaching success from a teacher to students at school, so that the principal and parents of students cannot know the success of teachers in teaching and guiding students. Realizing this problem, the writer is interested in building a decision support system by comparing 2 methods. Researchers will use the Weight Product and Simple Addictive Weighting methods. At this stage the results of the calculation of the Weight Product method will be compared with the results of the calculation of the Simple Additive Weighting method. Where the results of the comparison are that there are results that are not too significant but the results of the comparison are more dominant towards the SAW method. The accuracy of the SAW method reaches a value of 90% because there is a normalization process from the original alternative value. As for the WP method, it only uses a weighting of the existing alternatives.